Ekonomski vidik programa prizanesljivosti v Evropski uniji - Bokalič, Matej (LeXonomica, 2011)
Economic aspects of leniency program in European Union. Author deals with leniency program as a special concept of competition law and its economic aspects, especially in the connection with costs, economic influence on state budget and on cartel participants. He uses critical approach to evaluate the advantages and disadvantages of economic function of leniency program from the view of competition authorities and cartel participants. Author asserts that leniency program, despite its supposed positive effects on the effectiveness of competition authorities’ work in practice, theoretically has no chance for success if the effectiveness of competition authorities per se will not present a serious threat to disclose cartels and to sanction the cartel participants. Povzetek. V prispevku avtor obravnava program prizanesljivosti kot institut prava varstva konkurence in ekonomski pogled na ta program, zlasti v povezavi s stroškovnim vidikom organa varstva konkurence, ekonomskim vplivom na proračun, kamor se stekajo plačane globe, ter ekonomskim vplivom na v kartele udeležena podjetja. S kritičnim pristopom ovrednoti prednosti in slabosti ekonomske funkcije programa prizanesljivosti z vidika organa varstva konkurence in z vidika udeležencev kartela. Avtor opozarja, da program prizanesljivosti kljub domnevnim pozitivnim učinkom na učinkovitost dela organov varstva konkurence v praksi, teoretično nima možnosti za svoje temeljito poslanstvo, če učinkovitost organa varstva konkurence že per se ne bo predstavljala resne grožnje za odkritje kartelov in sankcioniranje udeležencev.